The The Influence of K3 Understanding on K3 Implementation in Motorcycle Engineering Expertise Competencies : The Influence of K3 Understanding on K3 Implementation in Motorcycle Engineering Expertise Competencies - Irfan Kurniawan; Shohihatur Rohman; Kriswanto (Universitas Pendidikan Ganesha, 2026)
This study aims to analyze the effect of Occupational Safety and Health understanding on the implementation of safety practices among students during workshop activities in the Motorcycle Engineering competency at SMK Muhammadiyah 2 Semarang, which is motivated by the low level of student safety behavior. The study employed a quantitative descriptive approach with a sample of 26 students. Data were collected through observation, interviews, and a 20-item Likert-scale questionnaire, and analyzed using validity, reliability, normality tests, and simple linear regression with SPSS. The results indicate that the instrument is valid and reliable with a Cronbach’s Alpha value above 0.80, and the data are normally distributed. Regression analysis shows that Occupational Safety and Health understanding has a significant effect on its implementation, with a significance value of less than 0.01 and a coefficient of determination of 0.601, indicating that 60.1 percent of safety practice implementation is influenced by students’ understanding, while the remaining is affected by other factors. These findings confirm that higher levels of safety understanding lead to better safety behavior during practical activities. This study highlights the importance of strengthening practice-based safety learning, developing consistent safe work habits, and enforcing supervision to improve safety implementation in vocational schools.the abstract in English here. If articles in English, abstract in Indonesia language do not need to be included. Writing abbreviations and mathematical formulas in the abstract needs to be avoided. The abstract consists of summary of the research objectives, approaches or methods used, important results and conclusions.